OPPORTUNITIES OF "MAPLE" SOFTWARE IN MATHEMATICS LESSONS IN SECONDARY SCHOOLS. METHODS OF SOLVING TRIGONOMETRICAL FUNCTIONS USING THE MAPLE PACKAGE - Feruza Bozorovna Khurramova (Galaxy International Interdisciplinary Research Journal, 2023)
This article focuses on the possibilities and methods of using the Maple program in math classes in secondary schools. Features of methods for solving trigonometric functions using the maple package. Methods of teaching the solution of trigonometric equations using a maple package in mathematics in secondary schools.